AN ANALYSIS OF STUDENTS' STRATEGIES IN PUBLIC SPEAKING SUBJECT BY USING STRATEGY INVENTORY FOR LANGUAGE LEARNING (SILL) - Suwarno, Widiya Juliyanti; Syaprizal; Ramasari, Maria (ELite Journal : International Journal of Education, Language and Literature, 2023)
This research aims to determine student learning strategies in learning English in public speaking subject through the Inventory Strategy for Language Learning (SILL) for second semester EFL students. The method used in this research was a descriptive quantitative approach. The population in this research was students in the second semester of English education, and the subjects of this study were 30 students of second semester of the English education study program for the 2021/2022 academic year at the University of PGRI Silampari. The data collection technique of this research used a questionnaire. The data analysis technique used in this research was the basic statistical technique of percentages using a likert scale questionnaire. The results of this research indicated that there were 11 students who used the "Metacognitive" learning strategy, 5 students used the "Cognitive" learning strategy, 8 students used the "Compensation" learning strategy, 6 students used the "Affective" learning strategy, 7 students used the "Social" learning strategy, there are no students used the "Memory" learning strategy.   Keywords: student learning strategies, SILL, Metacognitive, second semester students